A study of the illegal migrant workers in Malaysia: are more stringent measures needed? / Reen Rawaida Zuhdi, Asrinawati Ahmad Radzi and Nawal Yasmin Kamil - Zuhdi, Reen Rawaida; Ahmad Radzi, Asrinawati; Kamil, Nawal Yasmin (2005)
The purpose of this report is to identify the weaknesses of the law and the enforcement in combating the illegal entry. Other than that, this report also hopes to determine whether the present Act can deter illegal entry into Malaysia.